Akhlak dalam Perspektif Hadis: Sebuah Upaya Pencarian Relevansi Bagi Konteks Modern - Sukron Kamil (Refleksi: Jurnal Kajian Agama dan Filsafat, 2003)
The study of ethics, particularly from the perspective of hadith in a modern context, is crucial as it represents the second source of Islamic teachings after the Qur'an. An ethical study from the hadith perspective is relevant for understanding Islamic moral teachings and their application in daily life. Hadith, being the second source of Islamic guidance after the Qur'an, provides profound and relevant ethical guidance for various aspects of life, including addressing moral and social challenges in the modern era. The importance of studying ethics from the hadith perspective becomes more urgent when related to the situation in Indonesia, a predominantly Muslim country currently undergoing reforms in politics, economy, social, and cultural spheres. These reforms are a response to the economic crisis that triggered a political crisis, with moral crises such as corruption, collusion, and nepotism often seen as primary causes of these issues. In this context, understanding and applying the ethical values found in hadith can significantly contribute to restoring morality and integrity in society. This paper aims to explore how ethical teachings from hadith can be applied to address the moral and social challenges facing Indonesia today. Through text analysis of hadith and social-political context, this research will examine how hadith principles can help address moral crises and strengthen reform efforts across various sectors. This paper is expected to provide insights into the relevance of hadith ethics in the modern context and its contribution to solving moral issues in Indonesia.